Bone marrow derivation of pericryptal myofibroblasts in the mouse and human small intestine and colon. Issue 6 (1st June 2002) - Brittan, M; Hunt, T; Jeffery, R; Poulsom, R; Forbes, S J; Hodivala-Dilke, K; Goldman, J; Alison, M R; Wright, N A
Abstract : Background and aims: In order to establish whether extraintestinal cells contribute to the turnover and repair of gastrointestinal tissues, we studied the colons and small intestines of female mice that had received a male bone marrow transplant, together with gastrointestinal biopsies from female patients that had developed graft versus host disease after receiving a bone marrow transplant from male donors. Methods: Using in situ hybridisation to detect Y chromosomes and immunohistochemistry, we demonstrated that cells derived from injected bone marrow frequently engrafted into the intestine and differentiated into pericryptal myofibroblasts. Results: In the human intestine, we confirmed by combining in situ hybridisation with immunostaining for smooth muscle actin that the bone marrow derived cells within the intestine exhibited a myofibroblast phenotype. In female mouse recipients of male bone marrow grafts, we observed colocalisation of Y chromosomes and clusters of newly formed marrow derived myofibroblasts. While few of these were present at seven days after bone marrow transplantation, they were numerous at 14 days, and by six weeks entire columns of pericryptal myofibroblasts could be seen running up the sides of crypts in both the small intestine and colon. These columns appeared to extend into the villi in the small intestine. Within the intestinal lamina propria, these Y chromosome positive cells were negative for the mouse macrophage marker F4/80 antigen and CD34. Conclusions: Bone marrow derived pericryptal myofibroblasts were present in the mouse intestine following irradiation and bone marrow transplant, and in the intestines of human patients suffering graft versus host disease following a bone marrow transplant. Our data indicate that bone marrow cells contribute to the regeneration of intestinal myofibroblasts and epithelium after damage, and we suggest that this could be exploited therapeutically.